Pengembangan Virtual Laboratory pada Materi Inovasi Teknologi Biologi untuk Meningkatkan Pemahaman Konsep Siswa Kelas X SMA - Arica Pavitasari; Dian Puspita; Mar’atus Sholihah (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
This study aims to determine the feasibility and impact of virtual laboratories in learning the material of innovation in biological technology (biotechnology) for high school students in grade X. The feasibility assessment was carried out by three expert validators using a questionnaire instrument that measured aspects of material, media, and language and based on readability tests by teachers and students. The results of the study showed that the percentage of validity of the Virtual Laboratory from material experts was 95%, media experts 83%, language experts 90% with the third category being "Very Feasible". The results of the readability test from teachers obtained a percentage of 96% while the results of the readability test from students obtained a percentage of 99%. These results indicate that the Virtual Laboratory is Feasible and Practical to be used for biology learning, especially biotechnology material. The results of the teacher response test on the use of Virtual Laboratory showed a percentage of 95% while the results of the student response test were 75%. The results of the T test showed that Virtual Laboratory had a significant effect on students' conceptual understanding with a significance of 0.001. These results indicate that Virtual Laboratory is effective in improving students' conceptual understanding, especially in biotechnology material.